2009
DOI: 10.1590/s0102-76382009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Uso tópico de agente antifibrinolítico na redução do sangramento após revascularização cirúrgica do miocárdio

Abstract: Uso tópico de agente antifibrinolítico na redução do sangramento após revascularização cirúrgica do miocárdioTopical use of antifibrinolytic agent to reduce postoperative bleeding after coronary artery bypass surgery Abstract Objective: Antifibrinolytic agents reduce bleeding after cardiac surgery, but there are adverse effects after their systemic use. These effects are avoided by topical application of antifibrinolytic agents in pericardial cavity. We compared the effects of topically applied epsilon-aminoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was observed a lower bleeding and less need for blood transfusion, statistically significant. Breda et al [18] concluded that the topical use of antifibrinolytic agents in pericardial cavity of epsilonaminocaproic acid had a favorable effect in reducing bleeding in the first 24 hours postoperatively and in the need for blood transfusion after coronary artery bypass grafting when performed.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed a lower bleeding and less need for blood transfusion, statistically significant. Breda et al [18] concluded that the topical use of antifibrinolytic agents in pericardial cavity of epsilonaminocaproic acid had a favorable effect in reducing bleeding in the first 24 hours postoperatively and in the need for blood transfusion after coronary artery bypass grafting when performed.…”
Section: Discussionmentioning
confidence: 99%